The methodological quality of systematic reviews comparing temporomandibular joint disorder surgical and non-surgical treatment - Vasconcelos Belmiro CE; Bessa-Nogueira Ricardo V; Niederman Richard (BMC, 2008)
Abstract Background Temporomandibular joint disorders (TMJD) are multifactor, complex clinical problems affecting approximately 60-70% of the general population, with considerable controversy about the most effective treatment. For example, reports claim success rates of 70% and 83% for non-surgical and surgical treatment, whereas other reports claim success rates of 40% to 70% for self-improvement without treatment. Therefore, the purpose of this study was to (1) identify systematic reviews comparing temporomandibular joint disorder surgical and non-surgical treatment, (2) evaluate their methodological quality, and (3) evaluate the evidence grade within the systematic reviews. Methods A search strategy was developed and implemented for MEDLINE, Cochrane Library, LILACS, and Brazilian Dentistry Bibliography databases. Inclusion criteria were: systematic reviews (± meta-analysis) comparing surgical and non-surgical TMJD treatment, published in English, Spanish, Portuguese, Italian, or German between the years 1966 and 2007(up to July). Exclusion criteria were: in vitro or animal studies; narrative reviews or editorials or editorial letters; and articles published in other languages. Two investigators independently selected and evaluated systematic reviews. Three different instruments (AMSTAR, OQAQ and CASP) were used to evaluate methodological quality, and the results averaged. The GRADE instrument was used to evaluate the evidence grade within the reviews. Results The search strategy identified 211 reports; of which 2 were systematic reviews meeting inclusion criteria. The first review met 23.5 ± 6.0% and the second met 77.5 ± 12.8% of the methodological quality criteria (mean ± sd). In these systematic reviews between 9 and 15% of the trials were graded as high quality, and 2 and 8% of the total number of patients were involved in these studies. Conclusion The results indicate that in spite of the widespread impact of TMJD, and the multitude of potential interventions, clinicians have expended sparse attention to systematically implementing clinical trial methodology that would improve validity and reliability of outcome measures. With some 20 years of knowledge of evidence-based healthcare, the meager attention to these issues begins to raise ethical issues about TMJD trial conduct and clinical care.